Double Cationic‐Anionic Ordering in Ba‐Based Oxygen‐Deficient Perovskites1. Issue 6 (14th April 2015) - Raveau, Bernard; Caignaert, Vincent; Kundu, Asish K.
Abstract Complex cationic‐anionic ordering in barium‐based oxygen deficient perovskites is reviewed. Considering the parent ABO3 structure, the ordering between barium and a rare earth cation in the A site generates three classes of oxides, called double, triple and nanoscale ordered quintuple perovskites. From the ordering between a transition element (Fe, Co) and a larger cation on the B site two structural families are obtained, containing calcium and yttrium respectively. These oxides offer a vast playground for the investigation of magnetic and transport properties.